Efficacy of intrapleural instillation of fibrinolytics for treating pleural empyema and parapneumonic effusion: a meta‐analysis of randomized control trials. (16th January 2014) - Nie, Wencheng; Liu, Yanru; Ye, Jian; Shi, Liuhong; Shao, Fangchun; Ying, Kejing; Zhang, Ruifeng
Abstract Introduction The effects of intrapleural fibrinolysis for treating pleural empyema and parapneumonic effusion remain uncertain. Objectives We conducted a meta‐analysis of published randomized controlled trials (RCTs) to evaluate the efficacy of intrapleural instillation of fibrinolytics for treating pleural empyema and parapneumonic effusion. Methods Medline, Web of Science, Ovid and regulatory documents up to June 10, 2012 were searched. We selected RCTs on intrapleural fibrinolysis vs placebo control treatment for pleural empyema and parapneumonic effusion. The meta‐analysis was used to determine the odds ratios (OR) for death, surgical intervention and severe side effects, and weighted mean differences were used to estimate lengths of hospital stays. Results Ten trials with a total of 977 patients were included. Compared with a placebo, intrapleural fibrinolytic therapy decreased the OR for surgical intervention [OR = 0.24; 95% confidence interval (CI): 0.10–0.60] and the length of hospital stays (weighted mean difference = −6.47; 95% CI: −8.87, −4.08). Intrapleural fibrinolysis was associated with a non‐significant reduction in mortality rate (OR = 1.16; 95% CI: 0.71–1.89) and a non‐significant increase in severe side effects (OR = 1.92; 95% CI: 0.87–4.21). Subgroup analyses indicated that urokinase agents had marked positive effects on reducing surgical intervention (OR = 0.33; 95% CI: 0.14–0.78), but neither streptokinase nor tissue plasminogen activator did. Conclusions The present results show that intrapleural fibrinolysis with urokinase may be potentially effective for reducing the need for surgery. Intrapleural fibrinolytic therapy is effective for shortening the lengths of hospital stays without increasing the incidence of severe side effects.